2022
DOI: 10.3390/foods11162497
|View full text |Cite
|
Sign up to set email alerts
|

Application of Aloe vera Gel Coating Enriched with Cinnamon and Rosehip Oils to Maintain Quality and Extend Shelf Life of Pomegranate Arils

Abstract: A completely randomized design was applied on pomegranate arils for several post-harvest treatments before the packaging in polypropylene boxes for 15 days at (5 ± 1 °C, 95 ± 2% RH): control (untreated), Aloe vera gel (10% or 20%), 10% Aloe vera + rosehip oil (0.25% or 0.50%), 20% Aloe vera + rosehip oil (0.25% or 0.50%), 10% Aloe vera + cinnamon oil (0.25% or 0.50%), and 20% Aloe vera + cinnamon oil (0.25% or 0.50%). Aloe vera in combination with cinnamon oil resulted in an enhanced shelf life (15 d) compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
3
6
0
Order By: Relevance
“…Pomegranate products, including juice, wine, vinegar, and others, are widely accepted by consumers globally (Kalaycıoglu and Erim, 2017). Pomegranate juice, constituting 78% (w/w) (Singh et al, 2022) of fresh food products, exhibits three times higher antioxidant activity compared to wine and green tea (Arantino et al, 2023). In this study, the TPC, TFC and TMAC of 'Tunisia' and 'Qingpi' fruit juice were respectively 0.53-2.95 mg GAE/g, 0.84-2.55 mg RE/g, and 2.67-208.35 nmol/g, which were lower than 'Wonderful' pomegranate juice (Arantino et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate products, including juice, wine, vinegar, and others, are widely accepted by consumers globally (Kalaycıoglu and Erim, 2017). Pomegranate juice, constituting 78% (w/w) (Singh et al, 2022) of fresh food products, exhibits three times higher antioxidant activity compared to wine and green tea (Arantino et al, 2023). In this study, the TPC, TFC and TMAC of 'Tunisia' and 'Qingpi' fruit juice were respectively 0.53-2.95 mg GAE/g, 0.84-2.55 mg RE/g, and 2.67-208.35 nmol/g, which were lower than 'Wonderful' pomegranate juice (Arantino et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Martínez-Romero et al ( 2019) reported higher firmness values in REO coated plum fruit during storage at room conditions. Singh et al (2022) reported that applying REO combined with Aloe vera gel in the form of edible coating in pomegranate arils had higher firmness values than those without treatment.…”
Section: Fruit Flesh Firmness (Fff)mentioning
confidence: 99%
“…Previous studies have also reported that essential oil and Ca applications limit weight loss in fruit during storage. This effect is known to be successful in fruit by directly preserving both the physiological metabolism associated with ripening and the tissue firmness of the fruit (Shirzadeh et al, 2011;Paladines et al, 2014;Gago et al, 2016;Martínez-Romero et al, 2017;El-Dengawy et al, 2018;AL-Saikhan, 2018;Mahmoud et al, 2019;Martínez-Romero et al, 2019;Gemeda, 2021;Mazumder et al, 2021;Sati and Qubbaj, 2021;Singh et al, 2022). Saftner and Conway (1998) investigated the effects of postharvest CaCl 2 applications on the firmnesswater relations, cell wall calcium levels, and postharvest life of the apple.…”
Section: Weight Loss (Wl)mentioning
confidence: 99%
See 1 more Smart Citation
“…Pomegranate products, including juice, wine, vinegar, and others, are widely accepted by consumers globally (Kalaycıoglu and Erim, 2017). Pomegranate juice, constituting 78% (w/w) (Singh et al, 2022) of fresh food products, exhibits three times higher antioxidant activity compared to wine and green tea (Arantino et al, 2023). In this study, the TPC, TFC and TMAC of 'Tunisia' and 'Qingpi' fruit juice were respectively 0.53-2.95 mg GAE/g, 0.84-2.55 mg RE/g, and 2.67-208.35 nmol/g, which were lower than 'Wonderful' pomegranate juice (Arantino et al, 2023).…”
Section: A B D C Figurementioning
confidence: 99%